Obesity does not influence SARS-CoV-2 humoral vaccine immunogenicity - Mathieu D’Souza; Alexa Keeshan; Christopher A. Gravel; Marc-André Langlois; Curtis L. Cooper (npj Vaccines)
Abstract Obesity is a recognized factor influencing immune function and infectious disease outcomes. Characterization of the influence of obesity on SARS-CoV-2 humoral vaccine immunogenicity is required to properly tailor vaccine type (mRNA, viral-vector, protein subunit vaccines) and dosing schedule. Data from a prospective cohort study collected over 34 months was used to evaluate the slope of antibody production and decay and neutralizing capacity following SARS-CoV-2 vaccination in individuals with and without obesity at baseline. Most participants were female (65.4%), white (92.4%), and received mRNA vaccines. 210 were obese and 697 non-obese. Sex and infection-acquired immunity were identified as effect modifiers for the relationship between obesity and COVID-19 vaccine humoral immunogenicity. No consistent influence of obesity on peak titres, titre retention, antibody isotype (IgG, IgM, IgA), or neutralization was identified when controlling for other key variables. It may not be necessary to consider this variable when developing SARS-CoV-2 vaccine dosing strategies.